Performance of Two Commercial Assays for the Detection of Serum Aspergillus Galactomannan in Non-Neutropenic Patients - Rodrigo Almeida-Paes; Marcos de Abreu Almeida; Priscila Marques de Macedo; Diego H. Caceres; Rosely Maria Zancopé-Oliveira (Journal of Fungi, 2022)
Besides the relevance of aspergillosis in neutropenic patients, this mycosis has gained significance among non-neutropenic patients in last years. The detection of Aspergillus galactomannan has been used for aspergillosis diagnosis and follow-up in neutropenic patients. This study evaluated the applicability of two commercial tests for galactomannan detection in non-neutropenic patients with different clinical forms of aspergillosis. Serum samples from patients with chronic pulmonary aspergillosis, aspergilloma, invasive aspergillosis, and COVID-19 associated pulmonary aspergillosis were evaluated using the IMMY sōna AGM lateral flow assay and the Bio-Rad Platelia sandwich ELISA. Serum specimens from patients with tuberculosis, histoplasmosis, paracoccidioidomycosis, and from healthy individuals were used as controls. The Bio-Rad Platelia sandwich ELISA presented greater sensitivity, whereas the IMMY sōna AGM lateral flow assay presented greater specificity. The accuracies of the tests were similar, as demonstrated by a receiver operator characteristic analysis. Moreover, the best cut-off values determined by this analysis were closer to that recommended by both manufacturers for neutropenic patients. The galactomannan indexes determined by different methodologies were strongly related, and a substantial agreement was observed between results. Both tests can be used in non-neutropenic patients with the cut-off values defined by the manufacturers. Histoplasma cross-reactions may occur in areas where histoplasmosis is endemic.